Mediating role of self-regulatory efficacy on the relationship between punishment certainty, punishment severity and organizational deviance - Kura, Kabiru Maitama (Growing Science, 2014)
Several studies in the field of industrial and organizational psychology (I/O) have reported that workplace deviance is related to organization/work variables, such as organizational politics, perceived organizational support, job satisfaction, job stress, and organizational justice among others.However, relatively few studies have attempted to consider the relationship between organizational formal controls and workplace deviance.Even if any, they have reported mixed findings.Hence, a moderating variable is suggested.This paper proposes a moderating role of self-regulatory efficacy on the relationship between organizational formal controls and workplace deviance.